(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The essay sets out a number of issues for the purpose of a resumption of studies on neighbourhoods (compagne) and other organisms of lesser size and various orientations in Genoa in the late Middle Ages, with the aim of placing all the protagonists of city life in an "articulated topographical space", following the teaching of Edoardo Grendi. Attention is paid to the nature of the sources testifying to the framework of the divisions (whether institutional or not), to the terminology used, to the possible derivation of the organisms of later attestation (the conestagie) from previous collective experiences (viciniae, contratae, parishes).